The Influence Of Financial Performance, Macroeconomic Indicators And Systemic Risk On Manufacturing Sector Sharia Share Return - Rizky Siswanto; Sigid Eko Pramono; Rifki Ismal (Tazkia Islamic Finance and Business Review, 2021)
The purpose of this study is to examine and analyze the effect of financial performance as measured using Return On Assets (ROA), Current Ratio (CR) and Earning Per Share (EPS), macroeconomic indicators using the BI rate, exchange rate and inflation as well as adding systematic risk as the intervening variable on sharia stock returns in the manufacturing sector on the Indonesian Sharia Stock Index (ISSI). The research sample was 51 companies with a range of observations from 2016 to 2020, using the Structural Equation Modeling (SEM) method and IBM AMOS (Analysis of Structural Moment) V.22 software for testing the available data. The findings of the direct test results show that financial performance and systematic risk have an effect on Islamic stock returns, while macroeconomic indicators have no effect. The test results through the intervening variable found that financial performance had an effect, but macroeconomic indicators still had no effect on Islamic stock returns through systematic risk. Activities in the consumer goods industry and basic industry which have always been the main needs are the reason why issuers in the manufacturing sector at ISSI are not affected by changes in macroeconomic indicators. Keywords: Financial Performance, Macroeconomic Indicators, Systematic Risk, Islamic Stock, Returns